2001
DOI: 10.4049/jimmunol.167.10.5549
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Priming as a Predominant Mechanism for Inducing CD8+ T Cell Responses in Gene Gun DNA Immunization

Abstract: DNA immunization induces CD8+ CTL responses by bone marrow-derived APCs, which are directly transfected with a plasmid DNA and/or acquire Ags from DNA-transfected non-APCs. To investigate the relative contribution of DNA-transfected APCs vs non-APCs to the initiation of CD8+ T cell responses, we used tissue-specific promoter-directed gene expression and adoptive transfer systems in gene gun DNA immunization. In this study, we demonstrated that non-APC-specific gene expressions induced significant CD8+ CTL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 64 publications
6
77
2
Order By: Relevance
“…We propose that cross-priming may play a more pronounced role in loading Ag into LC that repopulate the GI site. This interpretation is consistent with findings from Cho et al (26), who addressed the role of crosspriming without direct transfection of LC, by demonstrating the ability to activate adoptively transferred Ag-specific CD8 T cells 7 and 21 days after GI, well after the first wave of LC migrated from the GI site. Although their data provide strong evidence that crosspriming plays a predominant role in generating humoral and cellular responses when using a keratinocyte promoter-driven GI vector, they did not directly examine the transfection of migratory cells from the GI site.…”
Section: Discussionsupporting
confidence: 80%
“…We propose that cross-priming may play a more pronounced role in loading Ag into LC that repopulate the GI site. This interpretation is consistent with findings from Cho et al (26), who addressed the role of crosspriming without direct transfection of LC, by demonstrating the ability to activate adoptively transferred Ag-specific CD8 T cells 7 and 21 days after GI, well after the first wave of LC migrated from the GI site. Although their data provide strong evidence that crosspriming plays a predominant role in generating humoral and cellular responses when using a keratinocyte promoter-driven GI vector, they did not directly examine the transfection of migratory cells from the GI site.…”
Section: Discussionsupporting
confidence: 80%
“…The difference in responses generated from TRP2 human IgG1 DNA compared to the protein equivalent suggests that the direct transfection of skin APC plays a role in the generation of these immune responses. The gene gun was initially believed to stimulate CTL by direct transfection of skin APC but has more recently been shown to also induce CTL via cross presentation [36,37]. We have also shown that the FcgR is important in generating high-avidity but not high-frequency responses from the DNA vaccination.…”
Section: Discussionmentioning
confidence: 87%
“…This is consistent with a previous report showing that the priming of CTLs using gene gun occurred through crosspriming and was independent of CD4 þ T-cell help. 42 However, the need for CD4 þ help in the priming of CTLs is still controversial, whereas recent data suggest that CD4 þ T help is needed for maintenance of a long-lived CTL response. 43 We have shown that the immunogenicity of the NS3 gene can be further improved by inclusion of NS4A.…”
Section: Codon Optimization and Rna Amplification For Hcv Ns3/4amentioning
confidence: 99%